Pengaruh Pembayaran Digital terhadap Pertumbuhan Ekonomi Indonesia: Analisis Moderasi Tingkat Pengangguran dan Inflasi - Arief Bachtiar; Dewi Sri Maulydia; Fajar Ramadhan; Rehan Isnan Purwandika (Journal of Trends Economics and Accounting Research, 2024)
This research aims to analyze the effect of non-cash payments and money supply on economic growth in Indonesia, considering unemployment and inflation as moderating variables. The data used in this research is in the form of semesterly data for the period 2009-2023, sourced from data presented by Bank Indonesia and BPS. This research used a quantitative approach with Moderated Regression Analysis (MRA) method which was analyzed using Eviews software. The result of this research suggest that non-cash payment has a Prob. of 0.003 (<0.05) and with positive coefficient of 1.390, and money supply has a Prob. of 0.000 (<0.05) with positive coefficient of 0.160. However, unemployment rate has a Prob. of 0.588 (>0.05), and inflation has a Prob. of 0.521 (>0.05). Furthermore, the interaction result between non-cash payment and unemployment rate has a Prob. of 0.032 (<0.05) with a negative coefficient of -0.134, and the interaction result between money supply and inflation has a Prob. of 0.302 (>0.05). Thus, it is obtained that non-cash payments and money supply has a significant positive effect on economic growth. Meanwhile, the unemployment rate and inflation directly has no significant effect on economic growth. Moreover, in the moderation analysis, the unemployment rate can moderate the effect of non-cash payments on economic growth. Conversely, inflation cannot moderate the effect of money supply on economic growth.